THE IMPORTANCE OF SKILLS AND COMPETENCIES IN THE PROFESSIONAL GROWTH OF TEACHERS (Konferensiyalar | Conferences, 2024)
The article discusses one of the ways to radically revise the training of a future specialist in higher education institutions, to improve the orientation of the pedagogical process in connection with changes in its content and structure -professional competence and the competence of a teacher. Based on the works of research scientists, the terms "competence", "professional competence" are analyzed, the formation of the qualities of scientific-methodological, professionalsubject, self-education, professional development, creative work, activity, responsibility in the educational process of a teacher is outlined.